Physeteroids from the Miocene of Peru: new data on Acrophyseter and Livyatan supports macroraptorial feeding in several extinct sperm whales - Lambert, Olivier; De Muizon, Christian; Urbina, Mario; Brian Beatty, L.; Di Celma, Claudio; BIANUCCI, GIOVANNI (Society of f Vertebrate Paleontology, 2015)
With only three extant species, modern sperm whales (Odontoceti, Physeteroidea) are generally considered as relicts of a previously more diversified clade, originating during the late Oligocene and reaching its maximum diversity in the Miocene. Displaying a spectacular size disparity, modern Kogia spp. (pygmy and dwarf sperm whales) and Physeter (giant sperm whale) share several morphological features (dental reduction, slender mandibles, and small temporal fossa) correlated to a specialized suction feeding technique on disphotic to mesopelagic prey. Although remaining scarce, the fossil record of sperm whales suggests a broader past ecological diversity; based on cranial and dental characters, several middle to late Miocene taxa (the medium size Acrophyseter, the large Brygmophyseter and Zygophyseter, and the giant Livyatan) were tentatively interpreted as macroraptorial feeders, using massive teeth deeply embedded in robust upper and lower jaws to catch proportionally large prey. Together with the study of two new Acrophyseter skulls, a detailed description of the type material of A. deinodon and L. melvillei (both originating from Miocene levels of the Pisco Formation, Peru) provides new clues about their hypothetical feeding strategies. The analysis of the specimens followed different lines: (1) basic craniomandibular anatomy and comparison; (2) reconstruction of the musculature for adduction/abduction of the mandibles; (3) bone pathology including the description of buccal maxillary exostoses in A. deinodon; and (4) tooth wear. Observations and resulting interpretations point to a feeding technique involving intense use of teeth via powerful bites, contrasting markedly with the capture technique in both Kogia and Physeter. Placed in a phylogenetic context, the morphology of the oral apparatus in these macroraptorial sperm whales is thought to represent a combination of plesiomorphic and derived characters. Finally, a detailed sedimentological and paleontological analysis of the fossil-rich localities of ...